Kinetic and Thermodynamic Properties of Biochanin A in Dimethyl Sulfoxide - Zhao, W.W. (Asian Journal of Chemistry, 2015)
In this paper, we measured the dissolution enthalpies of biochanin A in DMSO using a RD496-2000 Calvet microcalorimeter at 298.15 K under atmospheric pressure and the results show that the dissolution process possessed an endothermic behaviour. A series of thermodynamics functions and half-life period were obtained from thermodynamic and kinetic calculations. This work not only provides a simple method to determine the half-life period of a drug but also offers a theoretical guide for the clinical application of biochanin A.